Examining the association between self-confidence and coping strategies during menstruation in female soccer players: A cross-sectional study - Rosita, Nancy Diana; Muhammad, Heryanto Nur; Hidayat, Taufiq (Journal Sport Area, 2026)
Background: Menstrual-related symptoms may affect both physical performance and psychological readiness in female soccer players. However, limited research has examined the association between self-confidence and coping strategies during menstruation in competitive settings. Objectives: This study aimed to examine the association between self-confidence and coping strategies among female soccer players during menstruation. Methods: A quantitative cross-sectional correlational design was employed involving 24 female soccer players. Self-confidence was measured using the Trait Sport Confidence Inventory (TSCI), while coping strategies were assessed using the Brief COPE Inventory. Data were analysed using descriptive statistics, the Shapiro–Wilk test, and Pearson correlation analysis. Results: Participants showed relatively high levels of self-confidence (M = 21.04, SD = 1.90) and coping strategies (M = 27.08, SD = 2.32). A very strong positive correlation was found between the two variables (r = 0.858, p < 0.01), indicating a large effect size. Conclusion:  Coping strategies were strongly associated with self-confidence among female soccer players during menstruation. These findings suggest the importance of psychological factors in supporting athletes’ adaptation to physiological challenges, although causal relationships cannot be inferred due to the cross-sectional design.